2015
DOI: 10.1371/journal.pone.0141502
|View full text |Cite|
|
Sign up to set email alerts
|

Binge Ethanol and MDMA Combination Exacerbates Toxic Cardiac Effects by Inducing Cellular Stress

Abstract: Binge drinking is a common pattern of ethanol consumption among young people. Binge drinkers are especially susceptible to brain damage when other substances are co-administered, in particular 3,4 methylendioxymethamphetamine (MDMA). The aim of the present work was to study the mechanisms implicated in the adaptive changes observed after administration of these drugs of abuse. So, we have evaluated the cardiac sympathetic activity and the expression and activation of heat shock protein 27 (HSP27), after volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
(61 reference statements)
2
9
0
Order By: Relevance
“…Moreover, BD might increase the individuals’ risk of making ill-considered decisions about the use of illicit drugs. Finally, co-administration of alcohol and illicit drugs increases the risk of organ damage, especially in young adolescents 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BD might increase the individuals’ risk of making ill-considered decisions about the use of illicit drugs. Finally, co-administration of alcohol and illicit drugs increases the risk of organ damage, especially in young adolescents 28 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, alcohol did not significantly alter heat shock factor 1 (HSF1) (chronic alcohol) (61), Hsp25 (chronic alcohol) (58), Hsp 70 (chronic alcohol) (74), Hsp72 (chronic alcohol) (61), or Hsp90 (acute alcohol) (32). However, lower levels of alcohol intake in male mice increased total and phosphorylated Hsp27 (76). In contrast, work published before 2010 indicated that Hsp 60 and 70 were decreased in hearts from chronic alcohol-fed rats (77, 78).…”
Section: Oxidative Stressmentioning
confidence: 97%
“…MDMA and alcohol exposure in adolescent mice induced physiological and behavioural alteration than either drug administered alone [ 138 ]. In fact, recent study has shown that the co-abuse of MDMA and alcohol exacerbated cardiac cellular stress and toxicity through augmented activation of cardiac sympathetic system in adolescent mice ( Figure 2 ) [ 139 ]. MDMA can induce a rapid release of dopamine and serotonin [ 140 ].…”
Section: Alcohol and Mdma Co-abusementioning
confidence: 99%